Modulation for Hiperlan Type 2 - Thielecke, Jörn; et al. (IEEE Vehicular Technology Conference, 1999)
Currently, standards for wireless multimedia communication with high bit rate in the 5 GHz band are being developped in the U.S., Europe, and Japan. The available user data rate for these systems is supposed to be significantly greater than 10 Mbps. The high data rate and the channel characteristics are the main challenges for the design of the physical layer and in particular the selection of modulation technique for such a system. In this paper two modulation techniques, single-carrier and multicarrier modulation (implemented by OFDM), are considered as candidates. Both techniques are introduced, individually optimized to some extent and finally compared with regard to link performance and other aspects like coverage and power consumption. It is shown that for the assumed conditions the addressed coherent OFDM scheme provides about 2-3 dB performance gain compared to single-carrier modulation as well as non-coherent OFDM.
UnivIS-Import:2015-03-05:Pub.1999.tech.IE.komele.modula